Relationship between fluid-attenuated inversion-recovery (FLAIR) signal intensity and inflammatory mediator's levels in the hippocampus of patients with temporal lobe epilepsy and mesial temporal sclerosis - Pedro Paulo Vasconcellos Varella; Joselita Ferreira Carvalho Santiago; Henrique Carrete Jr.; Elisa Mieko Suemitsu Higa; Elza Márcia Targas Yacubian; Ricardo Silva Centeno; Luís Otávio Sales Ferreira Caboclo; Eduardo Ferreira de Castro Neto; Mauro Canzian; Débora Amado; Esper Abrão Cavalheiro; Maria da Graça Naffah- Mazzacoratti (Arquivos de Neuro-Psiquiatria)
We investigated a relationship between the FLAIR signal found in mesial temporal sclerosis (MTS) and inflammation. Twenty nine patients were selected through clinical and MRI analysis and submitted to cortico-amygdalo-hippocampectomy to seizure control. Glutamate, TNFα, IL1, nitric oxide (NO) levels and immunostaining against IL1β and CD45 was performed. Control tissues (n=10) were obtained after autopsy of patients without neurological disorders. The glutamate was decreased in the temporal lobe epilepsy (TLE) -MTS group (p<0.001), suggesting increased release of this neurotransmitter. The IL1β and TNFα were increased in the hippocampus (p<0.05) demonstrating an active inflammatory process. A positive linear correlation between FLAIR signal and NO and IL1β levels and a negative linear correlation between FLAIR signal and glutamate concentration was found. Lymphocytes infiltrates were present in hippocampi of TLE patients. These data showed an association between hippocampal signal alteration and increased inflammatory markers in TLE-MTS.